Isotopic evidence of increasing water abundance and lake hydrological change in Old Crow Flats, Yukon, Canada. (22nd November 2021) - MacDonald, Lauren A; Turner, Kevin W; McDonald, Ian; Kay, Mitchell L; Hall, Roland I; Wolfe, Brent B
Abstract: Lake-rich northern permafrost landscapes are sensitive to changing climate conditions, but ability to track real-time and potentially multiple hydrological responses (e.g. lake expansion, drawdown, drainage) is challenging due to absence of long-term, sustainable monitoring programs in these remote locations. Old Crow Flats (OCF), Yukon, is a Ramsar Wetland of International Importance where concerns about low water levels and their consequences for wildlife habitat and traditional ways of life prompted multidisciplinary studies during the International Polar Year (2007–2008) and led to the establishment of an aquatic ecosystem monitoring program. Here, we report water isotope data from 14 representative thermokarst lakes in OCF, the foundation of the monitoring program, and time-series of derived metrics including the isotope composition of input waters and evaporation-to-inflow ratios for a 13 year period (2007–2019). Although the lakes spanned multiple hydrological categories (i.e. rainfall-, snowmelt- and evaporation-dominated) based on initial surveys, well-defined trends from application of generalized additive models and meteorological records reveal that lakes have become increasingly influenced by rainfall, and potentially waters from thawing permafrost. These sources of input have led to more positive lake water balances. Given the documented role of rainfall in causing thermokarst lake drainage events in OCF and elsewhere, we anticipate increased vulnerability of lateral water export from OCF. This study demonstrates the value of long-term isotope-based monitoring programs for identifying hydrological consequences of climate change in lake-rich permafrost landscapes.